Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

Féminismes en terre vivante : entre écologie, luttes et savoirs autochtones - Institut de recherches et d'études féministes
Pour cette balade dans la foire féministe, nous explorons les liens entre féminisme, environnement et écologie. Quelle est la relation entre les luttes féministes et les enjeux environnementaux ? Quelles actions concrètes sont menées, et par quels organismes ? Quelle est la place des Premières Nations dans ces réflexions et mobilisations ? Nous vous invitons à cheminer avec nous à travers les différents ateliers de la foire pour découvrir ces croisements essentiels. Avec: Joséphine Bacon, Livia Vitenti, Laurie Gagnon-Bouchard, Milena Gioia, Marianne-Sarah Saulnier, Sophie-Laurence H. Lauzon, Martine Boivin, Claire Mur Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite).Un reportage écrit et monté par Rajae Anys, avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique; approches et analyses; autochtones; capitalisme; care; corps; discours dominant; foire féministe; groupes de femmes; justice environnementale; justice sociale; patriarcat; périodes historiques; québec; régions géographiques; santé; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; écoféminisme